THE USE OF DERIVATIVES AS FINANCIAL RISK MANAGEMENT INSTRUMENTS IN INDONESIAN MANUFACTURED COMPANIES - Purbasari, Intan (FEB Universitas Sultan Ageng Tirtayasa, 2018)
Companies need to manage the risks they face to achieve their goal of maximizing corporate value. One tool to manage risk is to hedge with derivative instruments. Knowing the significance of the effect of leverage, firm size, profitability and liquidity on hedging decision making in Manufacturing company is the purpose of this research. The Data that is used on this study is a set of data panel with purposive sampling method, and the criteria for the sample is: (1) manufacturing companies listed on the Stock Exchange period 2012 to 2016, (2) manufacturing companies that has transaction exposure ( liabilities and / or assets denominated in foreign currency, (3) manufacturing companies that has the data is needed for this study. The total sample of this study is 34 companies or 170 observation within 5 years. The Data analysis technique that is used on this study is logistic regression with z-statistic as hypotheses testing to test the regression coefficient with an alpha of 5%. The study result shows that firm size and liquidity positively and Significantly Affect the decision of hedging with foreign currency derivative instruments, while leverage negatively and insignificantly Affect the decision of hedging with foreign currency derivative instruments.